2016
DOI: 10.1007/jhep06(2016)114
|View full text |Cite
|
Sign up to set email alerts
|

Large mass hierarchies from strongly-coupled dynamics

Abstract: Besides the Higgs particle discovered in 2012, with mass 125 GeV, recent LHC data show tentative signals for new resonances in diboson as well as diphoton searches at high center-of-mass energies (2 TeV and 750 GeV, respectively). If these signals are confirmed (or other new resonances are discovered at the TeV scale), the large hierarchies between masses of new bosons require a dynamical explanation. Motivated by these tentative signals of new physics, we investigate the theoretical possibility that large hie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 98 publications
(141 reference statements)
2
30
1
Order By: Relevance
“…[9] 0.22(6) Ref. [19] 0.50 (26) to note that such smaller values have also been reported in other works, for example, in [43]. Note that the estimates of γ Ã discussed in this work show a remnant dependence on the gauge coupling, and are thus not precisely identical with the universal value at the IR fixed point.…”
Section: B Mode Numbercontrasting
confidence: 37%
See 1 more Smart Citation
“…[9] 0.22(6) Ref. [19] 0.50 (26) to note that such smaller values have also been reported in other works, for example, in [43]. Note that the estimates of γ Ã discussed in this work show a remnant dependence on the gauge coupling, and are thus not precisely identical with the universal value at the IR fixed point.…”
Section: B Mode Numbercontrasting
confidence: 37%
“…Even though all masses scale to zero, their ratios can be extrapolated to the conformal limit. It seems that these ratios are a universal characteristic for each (near) IR conformal theory [26].…”
Section: Chiral Symmetry Breaking Scenario and Conformality In Admentioning
confidence: 99%
“…On quite general grounds, in a confining theory one expects infinite numbers of such glueballs, that can be classified by quantum numbers of the Poincaré group (mass and spin), possibly supplemented by additional, model-dependent quantum numbers. The literature on the subject includes for instance the reviews in [1,2], and the detailed lattice studies in [3][4][5][6][7][8][9][10][11], besides suggestive ideas on general properties of the glueball spectra (the literature on which is vast, and deserves being reviewed elsewhere, but see for instance [12][13][14][15][16][17][18]). In more general theories, in which gluons couple to matter fields, the physical particles result from mixing between operators made purely of glue and other operators with the same quantum numbers.…”
Section: Introductionmentioning
confidence: 99%
“…Their existence is expected on general grounds in large classes of different theories, and their properties capture important information about the underlying dynamics. For example, it has been suggested that the ratio of the masses of the lightest spin-0 and spin-2 particles might highlight the existence of large mass hierarchies in some strongly coupled systems [15].…”
Section: Introductionmentioning
confidence: 99%